Audio-vestibular dysfunction in rheumatoid arthritis associated secondary Sjogren syndrome, and its correlation to serum level of anticardiolipin and muscarinic type 3 receptors antibodies: a cross-sectional observational study - Doaa Waseem Nada; Heba Ahmed Almokadem; Rania Elsaied Elkholy; Amani Mohamed El-Gharib; Marwa Ahmed Abdelwahab; Nema Ali Soliman; Alaa Mohamed Alsalawy (Egyptian Rheumatology and Rehabilitation)
Abstract Background In secondary Sjogren syndrome (sSS), the presence and extent of hearing and vestibular abnormalities are controversial. Hence, to ascertain if individuals with Rheumatoid arthritis (RA) associated secondary Sjogren syndrome (sSS) had subclinical audio-vestibular impairment as well as to investigate whether serum anticardiolipin and muscarinic receptors type 3 antibodies had a role in its pathogenesis, this cross-sectional study was conducted on 50 RA patients with secondary Sjogren syndrome manifestations and 50 RA patients without such manifestations were included, along with 50 apparently healthy volunteers who were aged, and sex-matched as controls. Full history taking, Otologic examination, Immunologic evaluation, and Audio-vestibular assessment were done for all subjects. Results Twenty-five percent of our patients experienced subjective audio-vestibular symptoms. In the audiogram, 30 (60%) of the 50 RA patients with sSS and 5 (10%) of RA patients without sSS had abnormal hearing loss compared to only 4 (8%) of the controls (p ≤ 0.001) with a predominance of high-frequency sensorineural hearing loss. Also, 20% of our patients experienced a higher frequency of head-shaking nystagmus than they did (p ≤ 0.001). 30% had a statistically significant increase in the frequency of abnormal caloric test results as compared to either controls (0%) or RA patients without sSS (0%); p ≤ 0.001 Finally, all audio-vestibular symptoms and tests exhibit a strong positive correlation with muscarinic receptors type 3 and anticardiolipin antibodies. Conclusion The use of muscarinic receptors type 3 and anticardiolipin antibodies are beneficial for early diagnosis of audio-vestibular dysfunction in RA-associated secondary Sjogren syndrome patients. Therefore, this study is important since it justifies rheumatologists’ screening for inner ear damage in their RA patients especially if associated with secondary Sjogren.